Comparison of clinical competency self‐assessments among Advanced Education in General Dentistry (AEGD) residents before and during COVID‐19 pandemic. Issue 7 (24th February 2022) - D'Emilio, Anna; Sabounchi, Shabnam Seyedzadeh; Wu, Yinxiang; Kim, Amy; Franck, Etienne; Kane, Daniel; Lieberman, Martin
Abstract: Purpose/objectives: Self‐assessment of clinical competence is an important tool for effective learning and training for some educational programs. The New York University (NYU) Langone Hospital's Advanced Education in General Dentistry (AEGD) Program has had its residents complete self‐assessment of clinical competency evaluations for many years. The evaluation is used to understand the residents' perception of their own clinical skill upon beginning the program and to determine the necessary resources to provide to the residents for them to meet program standards. The same evaluation is completed by the residents 6 months later to determine if they perceived advancement in their clinical performance while in the program. Dental education, along with other fields of education was disrupted by the coronavirus disease 2019 (COVID‐19) pandemic. The purpose of this study was to examine the impact of COVID‐19 on clinical competency self‐assessments among the NYU Langone AEGD residents before and during the pandemic. Methods: In this cross‐sectional study, data was collected from two AEGD cohorts representing 2019–2020 and 2020–2021 academic years; from July 2019 ( n = 196) to January 2020 ( n = 189) and July 2020 ( n = 202) to January 2021 ( n = 184). The self‐assessment evaluations were administered via an online residency management platform on the first days of July and January of the academic year. The survey consisted of 48 questions on "clinical skills and performance" as established by CODA standards for postdoctoral general dentistry programs. Results: Survey response rate was 100% for both cohorts. When comparing results, the findings indicate the COVID‐19 pandemic had interrupted clinical learning during dental school. However, training through the AEGD program led to improvements in perceived clinical competence by the residents in mid‐program evaluation. Conclusion: The self‐assessment evaluation can be used as a tool to enhance training as part of the AEGD program's performance improvement plan.